Analisis Peran Ekonomi Kreatif Berbasis Budaya Lokal Untuk Meningkatkan Pendapatan Pengrajin Kerawang Gayo Dalam Kajian Ekonomi Islam (Studi Kasus Pengrajin Kerawang Gayo di Kecamatan Bebesen, Kabupaten Aceh Tengah) - Ummu Khoirotun Nisfah; Sri Ramadhani; Muhammad Lathief Ilhamy Nasution (Universitas Labuhanbatu, 2023)
This study aims to analyze the role of local culture-based creative economy in the District of Bebesen, Central Aceh Regency to increase the income of the craftsmen filigree Gayo in the study of Islamic Economics. This study was a field study using qualitative descriptive methods; primary and secondary data sources were used, and data collection procedures included interviews, observations, and documentation. The subjects in this study were owners, artisans and several related village parties. Based on the results of the study showed the role of local culture-based creative economy run by the craftsmen filigree Gayo in the District Bebesen, Central Aceh district greatly assist the craftsmen in meeting their economic needs and can increase revenue compared to before running the business filigree Gayo. In running their business, the craftsmen are also on average have attended training from the government so that the quality and creativity and innovation can continue to grow so that it will have an impact on the level of income. As well as during their business, the craftsmen filigree Gayo has also applied the principles of Islamic Economics such as adl (Justice), Free Will, the principle of responsibility and truth so as not to harm either party. Considering Gayo Filigree is a superior local product in the region, this study was conducted in order to be able to make Gayo filigree into a local product that is known by the wider community and can continue to grow in the future, so as to continue to increase the income of Gayo filigree craftsmen.